Transobturator tape, tension‐free vaginal tape, and transvaginal tension‐free vaginal tape‐obturator for the treatment of female stress urinary incontinence: A systematic review and network meta‐analysis. Issue 3 (9th July 2021) - Wang, Huitao; Liu, Jinhong; Fang, Kewei; Liu, Jianhe; Chen, Tao; Yang, Tongxin; Shi, Xin
Abstract: Objective: To systematically review the safety and effectiveness of tension‐free vaginal tape (TVT), transobturator tape (TOT), and transvaginal tension‐free vaginal tape‐obturator (TVT‐O) in the treatment of stress urinary incontinence (SUI). Methods: The PubMed, Embase, The Cochrane Library, Web of Science, WanFang Data, and CNKI were electronically searched. A total of 22 trials involving 3709 patients were included. Results: The objective cure rate was better with TVT than with TOT and TVT‐O. The incidence of postoperative thigh/groin pain was lower with TVT than with TOT and TVT‐O, but the incidence of dysuria was higher with TVT than with TVT‐O. The incidence of lower urinary tract infection was higher with TVT than with TOT. Conclusion: Tension‐free vaginal tape may have a better outcome compared to TOT and TVT‐O, but the risk of dysuria and lower urinary tract infection is higher with SUI. Abstract : Compared with transobturator tape and transvaginal tension‐free vaginal tape‐obturator, tension‐free vaginal tape may have a better curative effect but higher risks of dysuria and lower urinary tract infection.